2020
DOI: 10.1002/adhm.202001245
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Ultralow Amount of Engineered Plant Viral Nanoparticles to Mesenchymal Stem Cells Enhances Osteogenesis and Mineralization

Abstract: Hydrogel-based materials are widely used to mimic the extracellular matrix in bone tissue engineering, although they often lack biofunctional cues. In the authors' previous work, Potato virus X (PVX), a flexible rod-shaped biocompatible plant virus nanoparticle (VNP) with 1270 coat protein subunits, is genetically modified to present functional peptides for generating a bone substitute. Here, PVX is engineered to present mineralization-and osteogenesis-associated peptides and laden in hydrogels at a concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 70 publications
(124 reference statements)
5
36
0
Order By: Relevance
“…Developing a new generation of hydrogel-inorganic particle stem cell composite implant materials improves the physical and biological properties of engineered bone and cartilage tissue [ 76 ]. Genetically modified potato virus X (PVX) nanoparticles can produce bone-related functional peptides, which are ideal materials for preparing hydrogel nanocomposites in bone tissue engineering [ 77 ].…”
Section: Surface Modification Of Plant Materials In the Spinementioning
confidence: 99%
“…Developing a new generation of hydrogel-inorganic particle stem cell composite implant materials improves the physical and biological properties of engineered bone and cartilage tissue [ 76 ]. Genetically modified potato virus X (PVX) nanoparticles can produce bone-related functional peptides, which are ideal materials for preparing hydrogel nanocomposites in bone tissue engineering [ 77 ].…”
Section: Surface Modification Of Plant Materials In the Spinementioning
confidence: 99%
“…In addition, viral nanotechnology is a powerful platform for specially controlled and programmed materials assembly for development of advanced biocatalytic materials [20–25] . Some prominent examples of plant viruses and bacteriophages utilized in viral nanotechnology include: virus‐like particles (VLPs, which are devoid of the viral genome) of Qβ and Physalis mottle virus (PhMV) [26,27] and VNPs from plants such as Cowpea mosaic virus (CPMV), Potato virus X (PVX), Turnip mosaic virus (TuMV) and Cowpea chlorotic mottle virus (CCMV) [28–35] . In particular, Tobacco mosaic virus (TMV) has been extensively analyzed for its reactivity and demonstrated as a robust platform in materials science, drug delivery, and structural biology [36–40] .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] Some prominent examples of plant viruses and bacteriophages utilized in viral nanotechnology include: viruslike particles (VLPs, which are devoid of the viral genome) of Qβ and Physalis mottle virus (PhMV) [26,27] and VNPs from plants such as Cowpea mosaic virus (CPMV), Potato virus X (PVX), Turnip mosaic virus (TuMV) and Cowpea chlorotic mottle virus (CCMV). [28][29][30][31][32][33][34][35] In particular, Tobacco mosaic virus (TMV) has been extensively analyzed for its reactivity and demonstrated as a robust platform in materials science, drug delivery, and structural biology. [36][37][38][39][40] Diverse applications have been made possible by the available chemical modification strategies.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Multivalent display of RGD on tobacco mosaic virus could upregulate bone differentiation makers. [15][16][17] Kang et al reported a charged mobile nanoligand to regulate cellular adhesion and differentiation. [18] Our previous study has shown that photocontrolled presentation of nanoclustered RGD using an upconversion substrate can guide multidirectional differentiation of MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, commercially available block copolymers comprising dispersed ligand clusters have been widely used to promote lineage‐specific differentiation of mesenchymal stem cells (MSCs) [11–14] . Multivalent display of RGD on tobacco mosaic virus could upregulate bone differentiation makers [15–17] . Kang et al.…”
Section: Introductionmentioning
confidence: 99%